Beam energy and centrality dependence of multiplicity fluctuations in heavy ion collisions. (January 2016) - Mukherjee, Maitreyee; Basu, Sumit; Choudhury, Subikash; Nayak, T K
Abstract: Multiplicity distributions of produced particles and their event-by-event fluctuations are studied using the AMPT model in the Default and String melting modes. In addition to being sensitive to the QCD phase transition, these fluctuations provide baselines for other event-by-event measurements. The collision energy and centrality dependence of fluctuations are estimated for heavy-ion collisions from √sNN =7.7 GeV to 2.76 TeV. The multiplicity fluctuations expressed in terms of scaled variance decreases from peripheral to central collisions for all energies, except for that of the Pb+Pb collisions at √sNN = 2.76 TeV. The beam energy dependence shows an increase of multiplicity fluctuations with increasing beam energy.